Free Convection in an Open Triangular Cavity Filled With a Nanofluid Under the Effects of Brownian Diffusion, Thermophoresis and Local Heater - Bondareva, Nadezhda S.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Asme, 2018)
Natural convection of a water-based nanofluid in a partially open triangular cavity with a local heat source of constant temperature under the effect of Brownian diffusion and thermophoresis has been analyzed numerically. Governing equations formulated in dimensionless stream function and vorticity variables on the basis of two-phase nanofluid model with corresponding initial and boundary conditions have been solved by finite difference method. Detailed study of the effect of Rayleigh number, buoyancy-ratio parameter, and local heater location on fluid flow and heat transfer has been carried out. It has been revealed that an increase in the buoyancy force magnitude leads to homogenization of nanoparticles distribution inside the cavity. A growth of a distance between the heater and the cavity corner illustrates the heat transfer enhancement.
Keywords: free convection; nanofluid; partially open triangular cavity; local heater; Brownian diffusion; thermophoresis